Flaky silver powder with low apparent density as well as preparation method and application of flaky silver powder
Through the combination of nano silver seeds and surfactants, sheet silver powder with narrow particle size distribution, low loose density and low burn rate were prepared, which solved the problems of unstable quality and poor electrical performance of sheet silver powder in the prior art, and met the demand for conductive pastes for electronic components.
Patent Information
- Application Number
- CN202510319087.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-18
AI Technical Summary
In the prior art, it is difficult to prepare sheet silver powder with narrow particle size distribution, low loose density and low burn rate, and traditional methods have problems such as unstable product quality and poor electrical performance.
The nano-silver seeds introduce spherical silver powder that regulates different particle sizes and sizes, add surfactants to promote monodispersion and assist grinding, and combine ball milling and washing steps to prepare thin flake-like low-loose density flake-like silver powder to control particle size distribution and loose density.
The sheet silver powder has a narrow particle size distribution, low loose density and low burn rate, which meets the use needs of conductive paste for electronic components and improves electrical performance and production efficiency.
Smart Images

Figure CN119819916A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal powder metallurgy, and in particular to a thin sheet-shaped low bulk density flaky silver powder and a preparation method and application thereof. Background Art
[0002] At present, flaky silver powder is one of the important materials for low-temperature curing conductive paste. It is mixed with organic adhesive resin and solvent to make a variety of conductive coatings and electronic pastes suitable for different scenarios. It is widely used in electronic components such as membrane switches, filters, flexible circuit boards, and semiconductor chip bonding. Due to the limitation of low-temperature curing process, silver powder cannot melt. Compared with the point-to-point contact of spherical silver powder, the conductive network formed by line contact or surface contact between flaky silver powders has low resistance and good conductivity. In addition, flaky silver powder has a wide deflection range and anti-fracture and elongation properties, and the electronic components produced are highly reliable. At the same time, the lower the bulk density of flaky silver powder, the lower the silver consumption required when using the same volume of silver powder, which can greatly reduce the amount of silver powder used and reduce the coating thickness, which is conducive to the miniaturization of electronic components; at the same time, the better the density of the slurry after low-temperature curing, the better the electrical properties.
[0003] The flaky silver powder is mainly prepared by mechanical ball milling in industry. The thickness of the flaky silver powder prepared by chemical method is only tens of nanometers. When the silver powder is prepared into electronic paste, it is heated and solidified during use, and the silver flake shrinks, resulting in holes, which reduces the electrical performance and has no practical value. The yield of flaky silver powder prepared by mechanical ball milling is high and it is easy to achieve batch scale-up. However, there are many control factors in mechanical ball milling, and the product quality is difficult to guarantee. At the same time, the flaky silver powder prepared by conventional ball milling is difficult to thin, has a wide particle size distribution, and has a high loose density, which is difficult to meet the demand for reducing silver consumption in electronic paste. At the same time, it leads to poor flatness of electronic paste printing, uneven printed circuits, and reduced electrical performance.
[0004] The invention patent application with publication number CN117961080A discloses a method for preparing flaky silver powder, the method comprising the following steps: mixing solution A and solution B and reacting them to prepare the flaky silver powder; wherein the solution A comprises Ag+, silver nanosheet seeds and ions with oxidizing effect, the solution B comprises ions with reducing effect, and the ions with oxidizing effect include Ce 4+ or Fe 3+ In the preparation process of the flaky silver powder of the present invention, no polymer dispersant or polymer surfactant is added, and the flaky silver powder is prepared by a one-step reduction method. Under the joint action of the oxidizing ions in the A solution and the silver nanosheet seeds, the flaky degree, surface smoothness and flatness of the prepared flaky silver powder are improved, thereby improving the conductive performance of the prepared flaky silver powder.
[0005] However, the flaky silver powder prepared by the preparation method described in the patent is relatively thin, only tens of nanometers thick, and often shrinks severely when configured into slurry in actual application, affecting the electrical properties and having no practical application value; at the same time, Ce is introduced during the preparation process. 4+ or Fe 3+ Impurity metal ions such as ions affect the purity and performance of the nano-silver flakes. In addition, during the preparation process of this patent, the nano-silver flakes are prone to aggregation, which affects their dispersion and stability. Summary of the invention
[0006] The present invention aims to provide a thin-flaked silver powder with low bulk density and a preparation method and application thereof, so as to prepare a flaked silver powder with high degree of flaking, narrow particle size distribution, high bulk density and low burnout rate at 538°C, so as to meet the use requirements of conductive paste for electronic components. Spherical silver powder with different particle sizes is prepared by regulating the introduction of nano silver crystal seeds, and a surfactant is introduced to promote the monodispersion of the spherical silver powder and play a role in aiding grinding, preventing sticking and narrowing the flake size distribution; the disadvantages of the traditional ball milling method such as poor stability, wide flake size distribution and low degree of flaking are overcome, and the production process is greatly shortened.
[0007] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows: The invention discloses a flaky silver powder prepared by the preparation method. The flaky silver powder with low bulk density is prepared by reducing a silver ammonia solution I to a nano silver seed solution, then mixing the nano silver seed solution with a silver ammonia solution II, and forming a spherical silver powder slurry through a reduction reaction; finally, ball milling, washing, drying and sieving the spherical silver powder slurry. The performance indicators of the flaky silver powder meet the following requirements: an average particle size D50 of 2 μm to 4 μm, a diameter-to-thickness ratio of 20:1 to 100:1, and a bulk density of 0.3 g / cm 3 ~0.6g / cm 3 ; Burning rate at 538℃ ≤0.9%.
[0008] A method for preparing flaky silver powder with low bulk density comprises the following steps: S1, preparation of nano silver seed crystals: adding silver ammonia solution I dropwise to dispersant solution, stirring for 5 min to 10 min after completion of the addition, to obtain mixed solution I, then adding reducing agent solution I dropwise to mixed solution I, stirring for 30 min to 40 min after completion of the addition, to obtain nano silver seed crystal solution; S2, adding the nano silver seed solution in step S1 to the surfactant solution, stirring and dispersing at a constant temperature for 5min to 10min to obtain a mixed solution II, and simultaneously dropping the silver ammonia solution II and the reducing agent solution II into the mixed solution II, and continuing the reaction for 5min to 10min after the dropwise addition is completed, and performing solvent replacement after the reaction is completed to obtain a spherical silver powder slurry; S3, adding the spherical silver powder slurry obtained in step S2 and the stainless steel grinding balls into a ball mill for ball milling, wherein the mass ratio of the spherical silver powder to the stainless steel grinding balls is 1:20-1:30; the diameter of the stainless steel grinding balls is 1 mm-3 mm, the external circulation system of the ball mill is started, the ball milling speed is 400 rpm-800 rpm, and the ball milling time is 4 h-8 h; S4. After ball milling, separate the flaky silver powder from the grinding balls, wash with deionized water to less than 20 μS / cm, dry at 70°C~80°C for 12h~24h, and then sieve through a sieve to obtain an average particle size D50: 2μm~4μm, a diameter-to-thickness ratio of 20:1~100:1, and a loose density of 0.3g / cm 3 ~0.6g / cm 3 Flake silver powder.
[0009] The dispersant solution is an aqueous solution of methyl cellulose or carboxymethyl cellulose or a mixture of the two.
[0010] The silver ammonia solution I and the silver ammonia solution II are both transparent Ag(NH3)2OH solutions prepared by adding ammonia water to a silver nitrate aqueous solution.
[0011] The reducing agent solution I and the reducing agent solution II are both aqueous glucose solutions.
[0012] The surfactant solution is an aqueous solution of any one or more mixtures of oleic acid, stearic acid, palmitic acid, palmitic acid and lauric acid.
[0013] In step S1, the mass concentration of silver ammonia in the silver ammonia solution I is 28 g / L~56 g / L; the mass concentration of the dispersant solution is 10 g / L~20 g / L; and the mass concentration of the reducing agent solution I is 15 g / L~36 g / L.
[0014] In step S1, the molar ratio of silver ammonia to reducing agent in the silver ammonia solution I and the reducing agent solution I is 1:0.5 to 1:0.6.
[0015] In the step S1, the dispersant solution, the reducing agent solution I and the silver ammonia solution I are preheated to 45°C to 55°C respectively, and the silver ammonia solution I and the reducing agent solution I are added dropwise at a temperature of 45°C to 55°C respectively. After the addition is completed, the reaction is stirred at a temperature of 45°C to 55°C.
[0016] In the step S1, the dropping speed of the silver ammonia solution I is 30 mL / min to 50 mL / min; the dropping speed of the reducing agent is 60 mL / min to 90 mL / min.
[0017] In step S2, the molar ratio of silver ammonia to reducing agent in the silver ammonia solution II and the reducing agent solution II is 1:0.5-1:0.6.
[0018] In the step S2, the silver ammonia solution II, the reducing agent solution II, the nano silver seed solution and the surfactant solution are preheated to 25°C-35°C respectively, the constant temperature stirring temperature is 25°C-35°C, and the silver ammonia solution II and the reducing agent solution II are added dropwise at a temperature of 25°C-35°C, and the reaction is continued at a temperature of 25°C-35°C after the addition is completed.
[0019] In step S2, the dropping speeds of the silver ammonia solution II and the reducing agent solution II are both 185 mL / min to 280 mL / min.
[0020] In step S2, the mass of the surfactant in the surfactant solution is 1.5% to 3% of the mass of the silver nitrate added to the silver ammonia solution II.
[0021] In step S2, the mass of the nano silver seed solution is 20% to 60% of the mass of the silver nitrate in the silver ammonia solution II.
[0022] In step S2, the solvent replacement is to use anhydrous ethanol to replace the aqueous solution, and the amount of anhydrous ethanol used is 1.18 times to 1.90 times the mass of silver nitrate added to the silver ammonia solution II.
[0023] In step S2, the mass concentration of silver ammonia in silver ammonia solution II is 318 g / L; the mass concentration of reducing agent solution II is 180 g / L; and the mass concentration of surfactant solution is 24 g / L-47 g / L.
[0024] In step S3, the cooling medium of the ball mill external circulation system is cold water, and the circulation speed is 0.5L / min~1L / min.
[0025] The invention discloses an application of flaky silver powder with low bulk density. The flaky silver powder with low bulk density prepared by the method for preparing the flaky silver powder with low bulk density is used for producing electronic silver paste.
[0026] Beneficial effects of the present invention: 1. In the present invention, by preparing nano silver seeds in advance, the nucleation and growth processes of silver particles are separated, so that the silver element generated in the subsequent redox reaction does not need to generate nuclei again, but grows with the nano silver seeds as the nucleus. The growth time is synchronized so that the particle size of the spherical silver particles is more concentrated, and finally the effect of narrowing the particle size distribution of the flaky silver powder is achieved. Spherical silver powders of different particle sizes and narrow particle size distribution can be prepared by adjusting the dosage of the nano silver seed solution; the spherical silver powder prepared by the present invention is almost in a monodisperse state, with a narrow particle size distribution, and a simple control method.
[0027] 2. In the present invention, a sufficient amount of surfactant is added during the preparation stage of spherical silver powder, which can not only ensure a good dispersion effect during the growth stage of the spherical silver powder, but also serve as a grinding aid in the subsequent grinding stage of flaky silver powder, thereby improving the lubrication effect of the grinding balls and the silver powder, improving the efficiency of spherical silver powder flake formation and breaking up large flaky silver powder; at the same time, it plays a steric role, avoiding adhesion between flakes to form large-sized flaky silver powder, thereby achieving the effect of narrowing the flake diameter.
[0028] 3. The present invention introduces nano silver seeds to make the particle size distribution of spherical silver particles narrower, so that the particle size is more concentrated when grinding flaky silver powder; the number of fine particles is reduced in the two stages of preparing spherical silver powder and flaky silver powder, so that the specific surface area is reduced, thereby reducing the number of adsorbed surfactants; and the free surfactants between the silver particles are removed in the washing step, so that the 538°C burnout rate is low.
[0029] 4. The preparation method of the present invention can realize the continuous production and preparation of spherical silver powder and flaky silver powder. After replacing the solvent with anhydrous ethanol, it can be directly used for grinding flaky silver powder. Compared with the traditional preparation method, the drying process of spherical silver powder is reduced, and the production efficiency is greatly improved; at the same time, the agglomeration and compaction of spherical silver powder during the drying process are avoided, which causes the flaky silver powder to be unable to disperse during the grinding process and cause the size to be too large.
[0030] 5. The flaky silver powder prepared by the present invention has a burning loss rate of ≤0.9% at 538°C and a bulk density of 0.3g / cm 3 ~0.6g / cm 3 , far lower than the national standard GB / T1773-2008 "Flake Silver Powder" 538℃ burning rate ≤ 2%, bulk density 1.2g / cm 3 ~2.5g / cm 3 performance indicators; the low 538℃ burnout rate of the flaky silver powder makes it configured into low-temperature curing silver paste printing, and less insulating material remains after curing, providing better electrical properties; the low bulk density of the flaky silver powder indicates that its flakes are thinner, and there are more surface overlaps to form pathways when configured into low-temperature curing silver paste printing and curing. At the same time, the flaky silver powder has higher sintering activity, so that it can still be partially sintered and melted even under the low-temperature curing process, forming better overlaps and providing good electrical properties, meeting the burnout rate and low bulk density requirements of the flaky silver powder under the process conditions of low-temperature curing silver paste for membrane switches.
[0031] 6. The present invention avoids overheating caused by the energy generated by the high-speed collision between the grinding ball and the spherical silver powder by externally circulating condensed water, and avoids the thickening of the sheet and the increase of the loose density caused by the adhesion and cold welding of the flaky silver powder due to excessive temperature.
[0032] 7. The flaky silver powder prepared by the method of the present invention has a narrow flake diameter distribution, a thin flake shape, a low bulk density, and a low ignition loss rate, which meets the use requirements of electronic pastes such as membrane switches / flexible circuit boards / varistors. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a scanning electron microscope image of the monodisperse spherical silver powder in the nanosilver seed solution prepared in Example 1 of the present invention.
[0034] Figure 2 This is a scanning electron microscope image of the thin flaky silver powder with low bulk density prepared by the present invention.
[0035] Figure 3 This is a scanning electron microscope image of flaky silver powder with a lower degree of flaking in the comparative example of the present invention.
[0036] Figure 4 This is a scanning electron microscope image of flaky silver powder with a relatively low diameter-to-thickness ratio in the comparative example of the present invention. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0038] Example 1 This embodiment provides a thin flaky silver powder with low bulk density, and the preparation method thereof comprises the following steps: S1. Add 10g of methylcellulose to 1000g of deionized water, stir to disperse and dissolve, and keep the temperature at 50°C to obtain a 10g / L dispersant solution A; add 8.7g of silver nitrate to 170g of deionized water, stir to dissolve, add ammonia water until it becomes colorless and transparent, and keep the temperature at 50°C to obtain a 48g / L silver ammonia solution IA; add 5.08g of anhydrous glucose to 180g of deionized water, stir to disperse and keep the temperature at 50°C to obtain a 28g / L reducing agent solution IA; then add the silver ammonia solution IA to the dispersant solution A at a flow rate of 40mL / min, stir for 5min, and obtain a mixed solution IA, then add the reducing agent solution IA to the mixed solution IA at a speed of 75mL / min, and continue to stir for 30min to obtain a nano silver seed solution A; Monodisperse spherical silver powder is obtained by taking a sample from the nano silver seed solution A with a pipette and drying it. The monodisperse spherical silver powder is subjected to a scanning electron microscope to obtain a scanning electron microscope image as shown in FIG. Figure 1 As shown; S2, add 189g silver nitrate to 556g deionized water, stir to dissolve and add ammonia water until colorless and transparent, keep constant temperature at 30°C, and obtain 318g / L silver ammonia solution ⅡA; add 110.26g anhydrous glucose to 612g deionized water, stir to dissolve and keep constant temperature at 30°C, and obtain 180g / L reducing agent solution ⅡA; add 3.6g stearic acid to 120g deionized water, stir to dissolve and keep constant temperature at 30°C, and obtain 30g / L surfactant solution A; 75.6 g of the nano silver seed solution A obtained in step S1 was added to the surfactant solution A to obtain a mixed solution IIA. After stirring and dispersing for 5 minutes, the silver ammonia solution IIA and the reducing agent solution IIA were simultaneously transferred to the mixed solution IIA at a rate of 280 mL / min. After the addition was completed, the reaction was continued for 10 minutes. After the reaction was completed, the aqueous solution was replaced with anhydrous ethanol, and the amount of anhydrous ethanol used was 1.48 times the mass of silver nitrate in the silver ammonia solution IIA to obtain a spherical silver powder slurry; S3, adding the spherical silver powder slurry obtained in step S2 and φ2 mm stainless steel grinding balls into a ball mill for ball milling, wherein the mass ratio of the spherical silver powder to the stainless steel grinding balls is 1:25, and starting the external circulation system of the ball mill, the ball milling speed is 600 rpm, and the ball milling time is 6 h; The cooling medium of the ball mill external circulation system is cold water, and the circulation speed is 1L / min; S4. After the ball milling is completed, the flaky silver powder is separated from the grinding balls, washed with deionized water to below 20 μS / cm, dried at 80° C. for 18 h, and then ultrasonically sieved using a 500-mesh sieve to obtain flaky silver powder.
[0039] The flaky silver powder obtained in this example was subjected to a scanning electron microscope to obtain a scanning electron microscope image as shown in FIG. Figure 2 shown.
[0040] In this embodiment, the flaky silver powder obtained in this embodiment is mixed with a halogen-free resin carrier to form an electronic paste with a silver content of 47%, which is printed on a 75μm PET substrate and then sintered and cured at 150°C / 30min. A film thickness meter and a digital multimeter are used to test the thickness of the electronic paste and calculate the square resistance. The resistance is 10.8mΩ / □ / mil, which meets the electrical performance requirements of the low-temperature curing paste for membrane switches.
[0041] Example 2 This embodiment provides a thin flaky silver powder with low bulk density, and the preparation method thereof comprises the following steps: S1. Add 20g of carboxymethyl cellulose to 1000g of deionized water, stir and disperse to dissolve and keep the temperature at 50°C to obtain 20g / L of dispersant solution B; add 5.1g of silver nitrate to 170g of deionized water, stir and disperse, add ammonia water until colorless and transparent, keep the temperature at 50°C to obtain 28g / L of silver ammonia solution IB; add 2.70g of anhydrous glucose to 180g of deionized water, stir and disperse and keep the temperature at 50°C to obtain 15g / L of reducing agent solution IB; then add the silver ammonia solution IB to the dispersant solution B at a flow rate of 30mL / min, stir for 10min, obtain a mixed solution IB, then add the reducing agent solution IB to the mixed solution IB at a speed of 60mL / min, continue stirring for 30min, and obtain a nano silver seed solution B; S2, add 189g silver nitrate to 556g deionized water, stir to dissolve and add ammonia water until colorless and transparent, keep constant temperature at 30°C, and obtain 318g / L silver ammonia solution IIB; add 100.24g anhydrous glucose to 556g deionized water, stir to dissolve and keep constant temperature at 30°C, and obtain 180g / L reducing agent solution IIB; add 2.83g oleic acid to 120g deionized water, stir to dissolve and keep constant temperature at 30°C, and obtain 24g / L surfactant solution B; 75.6 g of the nano silver seed solution B obtained in step S1 was added to the surfactant solution B to obtain a mixed solution IIB. After stirring and dispersing for 10 min, the silver ammonia solution IIB and the reducing agent solution IIB were simultaneously transferred to the mixed solution IIB at a rate of 185 mL / min. After the addition was completed, the reaction was continued for 10 min. After the reaction was completed, the aqueous solution was replaced with anhydrous ethanol, and the amount of anhydrous ethanol used was 1.48 times the mass of silver nitrate in the silver ammonia solution IIB to obtain a spherical silver powder slurry; S3, adding the spherical silver powder slurry obtained in step S2 and φ2 mm stainless steel grinding balls into a ball mill for ball milling, wherein the mass ratio of the spherical silver powder to the stainless steel grinding balls is 1:25, and starting the external circulation system of the ball mill, the ball milling speed is 600 rpm, and the ball milling time is 6 h; The cooling medium of the ball mill external circulation system is cold water, and the circulation speed is 1L / min; S4. After the ball milling is completed, the flaky silver powder is separated from the grinding balls, washed with deionized water to below 20 μS / cm, dried at 80° C. for 12 h, and then ultrasonically sieved using a 500-mesh sieve to obtain flaky silver powder.
[0042] In this embodiment, the flaky silver powder obtained in this embodiment is mixed with a halogen-free resin carrier to prepare an electronic paste with a silver content of 47%, which is printed on a 75μm PET substrate and then sintered and cured at 150°C / 30min. A film thickness meter and a digital multimeter are used to test the thickness of the electronic paste and calculate the square resistance. The resistance is 11.6mΩ / □ / mil, which meets the electrical performance requirements of the low-temperature curing paste for membrane switches.
[0043] Example 3 This embodiment provides a thin flaky silver powder with low bulk density, and the preparation method thereof comprises the following steps: S1. Add 15g of methylcellulose to 1000g of deionized water, stir to disperse and dissolve, and keep the temperature at 45°C to obtain a 15g / L dispersant solution C; add 10.2g of silver nitrate to 170g of deionized water, stir to dissolve, add ammonia water until colorless and transparent, and keep the temperature at 45°C to obtain a 56g / L silver ammonia solution IC; add 6.49g of anhydrous glucose to 180g of deionized water, stir to disperse and keep the temperature at 50°C to obtain a 36g / L reducing agent solution IC; then add the silver ammonia solution IC to the dispersant solution C at a flow rate of 50mL / min, stir for 10min, obtain a mixed solution IC, and then add the reducing agent solution IC to the mixed solution IC at a speed of 90mL / min, continue to stir for 30min, and obtain a nano silver seed solution C; S2, add 189g silver nitrate to 556g deionized water, stir to dissolve and add ammonia water until colorless and transparent, keep constant temperature at 25°C, and obtain 318g / L silver ammonia solution ⅡC; add 120.28g anhydrous glucose to 667g deionized water, stir to dissolve and keep constant temperature at 25°C, and obtain 180g / L reducing agent solution ⅡC; add 5.67g palmitic acid to 120g deionized water, stir to dissolve and keep constant temperature at 30°C, and obtain 47g / L surfactant solution C; 75.6 g of the nano silver seed solution C obtained in step S1 was added to the surfactant solution C to obtain a mixed solution IIC. After stirring and dispersing for 5 minutes, the silver ammonia solution IIC and the reducing agent solution IIC were simultaneously transferred to the mixed solution IIC at a rate of 225 mL / min. After the addition was completed, the reaction was continued for 10 minutes. After the reaction was completed, the aqueous solution was replaced with anhydrous ethanol, and the amount of anhydrous ethanol used was 1.48 times the mass of silver nitrate in the silver ammonia solution IIC to obtain a spherical silver powder slurry; S3, adding the spherical silver powder slurry obtained in step S2 and φ2 mm stainless steel grinding balls into a ball mill for ball milling, wherein the mass ratio of the spherical silver powder to the stainless steel grinding balls is 1:25, and starting the external circulation system of the ball mill, the ball milling speed is 600 rpm, and the ball milling time is 6 h; The cooling medium of the ball mill external circulation system is cold water, and the circulation speed is 0.8L / min; S4. After the ball milling is completed, the flaky silver powder is separated from the grinding balls, washed with deionized water to below 20 μS / cm, dried at 70° C. for 24 h, and then ultrasonically sieved using a 500-mesh sieve to obtain flaky silver powder.
[0044] In this embodiment, the flaky silver powder obtained in this embodiment is mixed with a halogen-free resin carrier to prepare an electronic paste with a silver content of 47%, which is printed on a 75μm PET substrate and then sintered and cured at 150°C / 30min. A film thickness meter and a digital multimeter are used to test the thickness of the electronic paste and calculate the square resistance. The resistance is 11.5mΩ / □ / mil, which meets the electrical performance requirements of the low-temperature curing paste for membrane switches.
[0045] Example 4 This embodiment provides a thin flaky silver powder with low bulk density, and the preparation method thereof comprises the following steps: S1. Add 20g of methylcellulose to 1000g of deionized water, stir and disperse to dissolve and keep the temperature at 55°C to obtain a 20g / L dispersant solution D; add 10.2g of silver nitrate to 170g of deionized water, stir and dissolve, add ammonia water until colorless and transparent, keep the temperature at 55°C to obtain a 56g / L silver ammonia solution ID; add 5.95g of anhydrous glucose to 180g of deionized water, stir and dissolve and keep the temperature at 55°C to obtain a 33g / L reducing agent solution ID; then add the silver ammonia solution ID to the dispersant solution D at a flow rate of 50mL / min, stir for 10min, obtain a mixed solution ID, then add the reducing agent solution ID to the mixed solution ID at a speed of 90mL / min, continue stirring for 40min, and obtain a nano silver seed solution D; S2, add 189g silver nitrate to 556g deionized water, stir to dissolve and add ammonia water until colorless and transparent, keep constant temperature at 35°C, and obtain 318g / L silver ammonia solution II D; add 110.26g anhydrous glucose to 612g deionized water, stir to dissolve and keep constant temperature at 35°C, and obtain 180g / L reducing agent solution II D; add 5.67g stearic acid to 120g deionized water, stir to dissolve and keep constant temperature at 30°C, and obtain 47g / L surfactant solution D; 75.6 g of the nano silver seed solution D obtained in step S1 was added to the surfactant solution D to obtain a mixed solution II D. After stirring and dispersing for 10 min, the silver ammonia solution II D and the reducing agent solution II D were simultaneously transferred to the mixed solution II D at a rate of 280 mL / min. After the addition was completed, the reaction was continued for 10 min. After the reaction was completed, anhydrous ethanol was used to replace the aqueous solution, and the amount of anhydrous ethanol used was 1.48 times the mass of silver nitrate in the silver ammonia solution II D to obtain a spherical silver powder slurry; S3, adding the spherical silver powder slurry obtained in step S2 and φ2 mm stainless steel grinding balls into a ball mill for ball milling, wherein the mass ratio of the spherical silver powder to the stainless steel grinding balls is 1:25, and starting the external circulation system of the ball mill, the ball milling speed is 600 rpm, and the ball milling time is 6 h; The cooling medium of the ball mill external circulation system is cold water, and the circulation speed is 0.5L / min; S4. After the ball milling is completed, the flaky silver powder is separated from the grinding balls, washed with deionized water to below 20 μS / cm, dried at 75° C. for 18 h, and then ultrasonically sieved using a 500-mesh sieve to obtain flaky silver powder.
[0046] In this embodiment, the flaky silver powder obtained in this embodiment is mixed with a halogen-free resin carrier to prepare an electronic paste with a silver content of 47%, which is printed on a 75μm PET substrate and then sintered and cured at 150°C / 30min. A film thickness meter and a digital multimeter are used to test the thickness of the electronic paste and calculate the square resistance. The resistance is 13.3mΩ / □ / mil, which meets the electrical performance requirements of the low-temperature curing paste for membrane switches.
[0047] Example 5 The present embodiment is different from the embodiment 1 in that, in the present embodiment, the dispersant solution E in step S1 is an aqueous solution of carboxymethyl cellulose; the surfactant solution E in step S2 is an aqueous solution of a mixture of stearic acid and lauric acid in a mass ratio of 2:1; and the remaining steps are the same as those in the embodiment 1.
[0048] Example 6 The present embodiment is different from the embodiment 1 in that, in the present embodiment, the dispersant solution F in step S1 is an aqueous solution of carboxymethyl cellulose; the surfactant solution F in step S2 is an aqueous solution of a mixture of oleic acid and palmitic acid in a mass ratio of 2:1; and the remaining steps are the same as those in the embodiment 1.
[0049] Example 7 The present embodiment is different from the embodiment 1 in that, in the present embodiment, the dispersant solution G in step S1 is an aqueous solution of methyl cellulose and carboxymethyl cellulose in a mass ratio of 1:1; the surfactant solution G in step S2 is an aqueous solution of stearic acid; and the remaining steps are the same as those in the embodiment 1.
[0050] Example 8 The present embodiment is different from the embodiment 1 in that, in the present embodiment, the dispersant solution H in step S1 is an aqueous solution of methyl cellulose and carboxymethyl cellulose in a mass ratio of 1:1; the surfactant solution H in step S2 is an aqueous solution of a mixture of palmitic acid and lauric acid in a mass ratio of 2:1; and the remaining steps are the same as those in the embodiment 1.
[0051] Example 9 The difference between this embodiment and embodiment 1 is that, in this embodiment, the mass of the nano silver seed solution A in step S2 is 37.8 g; the remaining steps are the same as those in embodiment 1.
[0052] Example 10 The difference between this embodiment and embodiment 1 is that, in this embodiment, the mass of the nano silver seed solution A in step S2 is 113.4 g; the remaining steps are the same as those in embodiment 1.
[0053] Embodiment 11 The difference between this embodiment and embodiment 1 is that, in this embodiment, the anhydrous ethanol used to replace the aqueous solution in step S2 is 1.18 times the mass of silver nitrate in the silver ammonia solution ⅡA; the remaining steps are the same as those in embodiment 1.
[0054] Example 12 The present embodiment is different from the embodiment 1 in that, in the present embodiment, the anhydrous ethanol used to replace the aqueous solution in step S2 is 1.90 times the mass of the silver nitrate in the silver ammonia solution ⅡA; the remaining steps are the same as those in the embodiment 1.
[0055] Embodiment 13 The present embodiment is different from the embodiment 1 in that, in the present embodiment, the mass ratio of the spherical silver powder to the stainless steel grinding balls in step S3 is 1:20; the size of the stainless steel grinding balls is φ1 mm; and the remaining steps are the same as those in the embodiment 1.
[0056] Embodiment 14 The present embodiment is different from the embodiment 1 in that, in the present embodiment, the mass ratio of the spherical silver powder to the stainless steel grinding balls in step S3 is 1:30; the size of the stainless steel grinding balls is φ3 mm; and the remaining steps are the same as those in the embodiment 1.
[0057] Embodiment 15 The difference between this embodiment and embodiment 1 is that, in this embodiment, the ball milling speed in step S3 is set to 400 rpm; the remaining steps are the same as those in embodiment 1.
[0058] Example 16 The difference between this embodiment and embodiment 1 is that, in this embodiment, the ball milling speed in step S3 is set to 800 rpm; the remaining steps are the same as those in embodiment 1.
[0059] Embodiment 17 The difference between this embodiment and embodiment 1 is that, in this embodiment, the ball milling time in step S3 is 4 hours; the remaining steps are the same as those in embodiment 1.
[0060] Embodiment 18 The difference between this embodiment and embodiment 1 is that, in this embodiment, the ball milling time in step S3 is 8 hours; the remaining steps are the same as those in embodiment 1.
[0061] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, the mass of the nanosilver seed solution A in step S2 is 18.9 g; the remaining steps are the same as those in Example 1.
[0062] Comparative Example 2 The difference between this comparative example and Example 1 is that in this comparative example, the mass of the nanosilver seed solution A in step S2 is 151.2 g; the remaining steps are the same as those in Example 1.
[0063] Comparative Example 3 The difference between this comparative example and Example 1 is that in this comparative example, the anhydrous ethanol used to replace the aqueous solution in step S2 is 2.54 times the mass of silver nitrate in the silver ammonia solution ⅡA; the remaining steps are the same as those in Example 1.
[0064] Comparative Example 4 The difference between this comparative example and Example 1 is that in this comparative example, the anhydrous ethanol used to replace the aqueous solution in step S2 is 0.95 times the mass of silver nitrate in the silver ammonia solution ⅡA; the remaining steps are the same as those in Example 1.
[0065] Comparative Example 5 The difference between this comparative example and Example 1 is that in this comparative example, the surfactant in step S2 is 1.2 g of stearic acid; 1.2 g of stearic acid is added to 120 g of deionized water, stirred to dissolve and kept at a constant temperature of 30°C to obtain a 10 g / L surfactant solution I; the remaining steps are the same as in Example 1.
[0066] Comparative Example 6 The difference between this comparative example and Example 1 is that in this comparative example, the surfactant in step S2 is 8.4 g of stearic acid; 8.4 g of stearic acid is added to 120 g of deionized water, stirred to dissolve and kept at a constant temperature of 30°C to obtain 70 g / L surfactant solution J; the remaining steps are the same as in Example 1.
[0067] Comparative Example 7 The difference between this comparative example and Example 1 is that in this comparative example, the mass ratio of the spherical silver powder to the stainless steel grinding balls in step S3 is 1:10; the remaining steps are the same as those in Example 1.
[0068] Comparative Example 8 The difference between this comparative example and Example 1 is that in this comparative example, the mass ratio of the spherical silver powder to the stainless steel grinding balls in step S3 is 1:40; and the remaining steps are the same as those in Example 1.
[0069] Comparative Example 9 The difference between this comparative example and Example 1 is that in this comparative example, the ball milling time in step S3 is 3 hours; the remaining steps are the same as in Example 1.
[0070] The flaky silver powder obtained in this comparative example was subjected to a scanning electron microscope to obtain a scanning electron microscope image as shown in FIG. Figure 3 shown.
[0071] Comparative Example 10 The difference between this comparative example and Example 1 is that in this comparative example, the ball milling time in step S3 is 8 hours; the remaining steps are the same as in Example 1.
[0072] Comparative Example 11 The difference between this comparative example and Example 1 is that in this comparative example, the ball milling speed in step S3 is 300 rpm; the remaining steps are the same as in Example 1.
[0073] Comparative Example 12 The difference between this comparative example and Example 1 is that in this comparative example, the ball milling speed in step S3 is 1000 rpm; the remaining steps are the same as in Example 1.
[0074] Comparative Example 13 The difference between this comparative example and Example 1 is that in this comparative example, the reducing agent solution IK and the reducing agent solution IIK in steps S1 and S2 are both aqueous solutions of hydrazine hydrate; and the remaining steps are the same as those in Example 1.
[0075] Comparative Example 14 The difference between this comparative example and Example 1 is that in this comparative example, the dispersant in step S1 is polyvinyl pyrrolidone K90; and the remaining steps are the same as those in Example 1.
[0076] Comparative Example 15 The difference between this comparative example and Example 1 is that in this comparative example, the surfactant in step S2 is oleylamine; and the remaining steps are the same as those in Example 1.
[0077] The flaky silver powder obtained in this comparative example was subjected to a scanning electron microscope to obtain a scanning electron microscope image as shown in FIG. Figure 4 shown.
[0078] Experimental example In this experimental example, the spherical silver powder mass was obtained by the following steps using Examples 1 to 18 and Comparative Examples 1 to 15: The laser particle size data, 538°C burnout rate data and tap density data of the flaky silver powder obtained in Examples 1 to 18 and Comparative Examples 1 to 15 are listed in Table 1; The 538℃ burnout rate is determined in accordance with the national standard GB / T1773-2008: 3.0g of sample is placed in a crucible with constant weight, placed in a tubular resistance furnace, heated to 538℃, kept at 538℃±5℃ for 30min, cut cold in the furnace, taken out and weighed, and the burnout rate (X2) is calculated according to formula (2), and the value is expressed in %: Where: m3——the weight of the sample before burning, in grams (g); m4——the weight of the sample after burning, in grams (g); The burn-in rate represents the proportion of non-silver components in silver powder, such as organic component coating agents, etc. These substances often reduce the electrical performance in the circuit, but will play a role in adjusting the compatibility, adaptability, viscosity, etc. of the slurry when it is configured into a slurry. Therefore, it is necessary to ensure that the burn-in rate is at a lower value.
[0079] Table 1 Data of the flake silver powder obtained in Examples 1 to 18 and Comparative Examples 1 to 15 As can be seen from Table 1, compared with Comparative Examples 1 to 15, the flaky silver powder prepared in Examples 1 to 18 is more in line with the use requirements of the membrane switch low-temperature curing silver paste use process conditions for flaky silver powder in terms of particle size distribution, 538°C burn-in rate, bulk density, tap density, diameter-to-thickness ratio and other parameters.
[0080] Figure 1 This is a scanning electron microscope image of the monodisperse spherical silver powder in the nanosilver seed solution A prepared in Example 1. It can be seen that the spherical silver powder prepared by this method has a concentrated particle size distribution, high sphericity, and good dispersibility, which is conducive to obtaining flaky silver powder with narrow flake diameter distribution and good dispersibility when subsequently grinding flaky silver powder.
[0081] Figure 2 This is a scanning electron microscope image of the thin flaky silver powder with low loose density prepared in Example 1. When the preparation is configured for low-temperature curing silver paste printing and curing, there are more surface overlaps to form pathways. At the same time, the thin flaky silver powder has higher sintering activity, so that it can still be partially sintered and melted even under the low-temperature curing process, forming better overlaps and providing good electrical properties, thus meeting the use requirements of the flaky silver powder put forward by the process conditions of the low-temperature curing silver paste of the membrane switch.
[0082] Figure 3This is a scanning electron microscope image of the flaky silver powder with a low degree of flaking prepared in Comparative Example 9. When configured for low-temperature curing silver paste printing and curing, due to the low degree of flaking and low sintering activity, the degree of melting after curing is low, and some particles are in point-to-point contact or point-to-line contact, resulting in poor electrical properties, which does not meet the use requirements of the flaky silver powder proposed by the process conditions of low-temperature curing silver paste for membrane switches.
[0083] Figure 4 This is a scanning electron microscope image of the flaky silver powder with a relatively low diameter-thickness ratio prepared in Comparative Example 15. When configured for low-temperature curing silver paste printing and curing, due to the relatively high diameter-thickness ratio, the sintering activity at the edge of the flaky silver powder is relatively weak, and the degree of melting is low during low-temperature curing, making it difficult to effectively melt and bond the circuit, resulting in poor electrical performance. This does not meet the use requirements of the flaky silver powder in the process conditions for the use of low-temperature curing silver paste for membrane switches.
[0084] Compared with Example 1, Comparative Example 1 has a low dosage of nano silver seeds, which results in a larger size of the synthesized spherical silver powder, which in turn results in an increase in the particle size of the obtained flaky silver powder and a decrease in the degree of flaking, resulting in a high bulk density and a high tap density, which does not meet the use requirements of the low-temperature curing silver paste for membrane switches.
[0085] Compared with Example 1, Comparative Example 2 has a high dosage of nano silver seeds, which results in a smaller size of the synthesized spherical silver powder, which in turn results in a smaller particle size of the obtained flaky silver powder and adsorption of more surfactants, resulting in a higher burnout rate at 538°C, which does not meet the use requirements of low-temperature curing silver paste for membrane switches.
[0086] Compared with Example 1, Comparative Example 3 has a low amount of anhydrous ethanol, resulting in a high solid content when grinding the flaky silver powder. The spherical silver particles are cold welded to form large pieces during the extension process, resulting in the flaky silver powder having a larger particle size and a wider particle size distribution, which does not meet the use requirements of the low-temperature curing silver paste for membrane switches.
[0087] Compared with Example 1, Comparative Example 3 has a low amount of anhydrous ethanol, resulting in a high solid content when grinding the flaky silver powder. The spherical silver particles are easily collided and cold welded to form large pieces during the extension process, resulting in the flaky silver powder having a larger particle size and a wider particle size distribution, which does not meet the use requirements of the low-temperature curing silver paste of the membrane switch.
[0088] Compared with Example 1, Comparative Example 4 has a high dosage of anhydrous ethanol, resulting in a low solid content when grinding the flaky silver powder. The spherical silver particles are subjected to the resistance of anhydrous ethanol during the extension process, which reduces the collision energy between the grinding balls and the silver particles, resulting in a low degree of flake silver powder and a low diameter-to-thickness ratio. At the same time, the loose density and tap density are high, which does not meet the use requirements of the low-temperature curing silver paste of the membrane switch.
[0089] Compared with Example 1, Comparative Example 5 has a low amount of surfactant, resulting in insufficient dispersion effect of the spherical silver powder during the preparation process, making the size of the spherical silver particles larger. At the same time, when grinding the flaky silver powder, the flaky silver powder lacks the dispersing effect of the surfactant, resulting in the flaky silver powder being larger in size, which does not meet the use requirements of the low-temperature curing silver paste of the membrane switch.
[0090] Compared with Example 1, Comparative Example 6 has a high dosage of surfactant, which leads to a good dispersion effect of the spherical silver powder during the preparation process, making the size of the spherical silver particles smaller. At the same time, it plays a lubricating role when grinding the flaky silver powder, making the flaky silver powder small in size and thin in shape, thereby absorbing more surfactants, resulting in a high burnout rate at 538°C, which does not meet the use requirements of low-temperature curing silver paste for membrane switches.
[0091] Compared with Example 1, Comparative Examples 7, 9 and 11 have low ball-to-material ratio, short ball milling time and low ball milling speed, so that the energy of the spherical silver particles deformed by the milling balls is too small, resulting in too low a degree of flaking of the spherical silver powder. The final product is a mixture of thin flake powder and spherical silver particles that are almost not flaked. The statistical diameter-to-thickness ratio has no practical significance, resulting in high bulk density and tap density of the flaky silver powder, which does not meet the use requirements of low-temperature curing silver paste for membrane switches.
[0092] Compared with Example 1, Comparative Examples 8, 10 and 12 have high ball-to-material ratio, long ball milling time and high ball milling speed, so that the energy of deformation of the spherical silver particles caused by the milling balls is too high, resulting in excessive flake degree of the spherical silver powder, resulting in a high 538°C burnout rate of the flaky silver powder, which does not meet the use requirements of low-temperature curing silver paste for membrane switches.
[0093] Compared with Example 1, Comparative Example 13 has a strong reducing ability of the reducing agent hydrazine hydrate, which leads to smaller size of the nano silver seeds and spherical silver particles during the forming process. As a result, the specific surface area increases when grinding the flaky silver powder, and more surfactants are adsorbed, resulting in a higher 538°C burnout rate of the flaky silver powder, which does not meet the use requirements of low-temperature curing silver paste for membrane switches.
[0094] Compared with Example 1, Comparative Example 14 has a weaker dispersing effect of polyvinyl pyrrolidone, resulting in a larger size of the nanosilver seed particles. As a result, when the same mass of nanosilver seed solution is used, the number of nanosilver particles is smaller, the spherical silver particles are larger, and the size of the flaky silver powder is larger. The particle size distribution becomes wider, which does not meet the use requirements of low-temperature curing silver paste for membrane switches.
[0095] Compared with Example 1, since the adsorption effect of amino group in oleylamine on silver is not as good as the adsorption effect of carboxyl group in organic acid on silver, the surface energy of silver particles is reduced or dislocation migration of the lattice near the surface layer is caused, and the effect of reducing the strength and hardness of silver particles is not as good as that of organic acid grinding aids, resulting in a low degree of flaking of spherical silver powder under the same ball milling energy, resulting in high loose density and tap density of flaky silver powder, which does not meet the use requirements of low-temperature curing silver paste for membrane switches.
[0096] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.
Claims
1. A thin flake silver powder with low bulk density, characterized in that: The flaky silver powder is prepared by reducing a silver ammonia solution I to a nano silver seed solution, then mixing the nano silver seed solution with a silver ammonia solution II, and forming a spherical silver powder slurry through a reduction reaction; finally, ball milling, washing, drying and sieving the spherical silver powder slurry. The performance indicators of the flaky silver powder meet the following requirements: an average particle size D50 of 2 μm to 4 μm, a diameter-to-thickness ratio of 20:1 to 100:1, and a bulk density of 0.3 g / cm 3 ~0.6g / cm 3 ; Burning rate at 538℃ ≤0.9%.
2. A method for preparing the flaky silver powder with low bulk density as claimed in claim 1, characterized in that: The steps include: S1, preparation of nano silver seed crystals: adding silver ammonia solution I dropwise to dispersant solution, stirring for 5 min to 10 min after completion of the addition, to obtain mixed solution I, then adding reducing agent solution I dropwise to mixed solution I, stirring for 30 min to 40 min after completion of the addition, to obtain nano silver seed crystal solution; S2, adding the nano silver seed solution in step S1 to the surfactant solution, stirring and dispersing at a constant temperature for 5min to 10min to obtain a mixed solution II, and simultaneously dropping the silver ammonia solution II and the reducing agent solution II into the mixed solution II, and continuing the reaction for 5min to 10min after the dropwise addition is completed, and performing solvent replacement after the reaction is completed to obtain a spherical silver powder slurry; S3, adding the spherical silver powder slurry obtained in step S2 and the stainless steel grinding balls into a ball mill for ball milling, wherein the mass ratio of the spherical silver powder to the stainless steel grinding balls is 1:20-1:30; the diameter of the stainless steel grinding balls is 1 mm-3 mm, the external circulation system of the ball mill is started, the ball milling speed is 400 rpm-800 rpm, and the ball milling time is 4 h-8 h; S4. After ball milling, separate the flaky silver powder from the grinding balls, wash with deionized water to less than 20 μS / cm, dry at 70°C~80°C for 12h~24h, and then sieve through a sieve to obtain an average particle size D50: 2μm~4μm, a diameter-to-thickness ratio of 20:1~100:1, and a loose density of 0.3g / cm 3 ~0.6g / cm 3 Flake silver powder.
3. The method for preparing the flaky silver powder with low bulk density according to claim 2, characterized in that: The dispersant solution is an aqueous solution of methyl cellulose or carboxymethyl cellulose or a mixture of the two.
4. The method for preparing the flaky silver powder with low bulk density according to claim 2, characterized in that: The silver ammonia solution I and the silver ammonia solution II are both transparent Ag(NH3)2OH solutions prepared by adding ammonia water to silver nitrate aqueous solution; the reducing agent solution I and the reducing agent solution II are both glucose aqueous solutions.
5. The method for preparing the flaky silver powder with low bulk density according to claim 2, characterized in that: The surfactant solution is an aqueous solution of any one or more mixtures of oleic acid, stearic acid, palmitic acid, palmitic acid and lauric acid.
6. The method for preparing the flaky silver powder with low bulk density according to any one of claims 3 to 5, characterized in that: In step S1, the mass concentration of silver ammonia in the silver ammonia solution I is 28 g / L~56 g / L; the mass concentration of the dispersant solution is 10 g / L~20 g / L; and the mass concentration of the reducing agent solution I is 15 g / L~36 g / L.
7. The method for preparing the flaky silver powder with low bulk density according to claim 6, characterized in that: In step S1, the molar ratio of silver ammonia to reducing agent in the silver ammonia solution I and the reducing agent solution I is 1:0.5 to 1:0.
6.
8. The method for preparing the flaky silver powder with low bulk density according to claim 7, characterized in that: In the step S1, the dispersant solution, the reducing agent solution I and the silver ammonia solution I are preheated to 45°C to 55°C respectively, and the silver ammonia solution I and the reducing agent solution I are added dropwise at a temperature of 45°C to 55°C respectively. After the addition is completed, the reaction is stirred at a temperature of 45°C to 55°C.
9. The method for preparing the flaky silver powder with low bulk density according to claim 8, characterized in that: In the step S1, the dropping speed of the silver ammonia solution I is 30 mL / min to 50 mL / min; the dropping speed of the reducing agent is 60 mL / min to 90 mL / min.
10. The method for preparing the flaky silver powder with low bulk density according to claim 4, characterized in that: In step S2, the molar ratio of silver ammonia to reducing agent in the silver ammonia solution II and the reducing agent solution II is 1:0.5-1:0.
6.
11. The method for preparing the flaky silver powder with low bulk density according to claim 10, characterized in that: In the step S2, the silver ammonia solution II, the reducing agent solution II, the nano silver seed solution and the surfactant solution are preheated to 25°C-35°C respectively, the constant temperature stirring temperature is 25°C-35°C, and the silver ammonia solution II and the reducing agent solution II are added dropwise at a temperature of 25°C-35°C, and the reaction is continued at a temperature of 25°C-35°C after the addition is completed.
12. The method for preparing the flaky silver powder with low bulk density according to claim 11, characterized in that: In step S2, the dropping speeds of the silver ammonia solution II and the reducing agent solution II are both 185 mL / min to 280 mL / min.
13. The method for preparing the flaky silver powder with low bulk density according to claim 4, characterized in that: In step S2, the mass of the surfactant in the surfactant solution is 1.5% to 3% of the mass of the silver nitrate added to the silver ammonia solution II.
14. The method for preparing the flaky silver powder with low bulk density according to claim 4, characterized in that: In step S2, the mass of the nano silver seed solution is 20% to 60% of the mass of the silver nitrate added to the silver ammonia solution II.
15. The method for preparing the flaky silver powder with low bulk density according to claim 4, characterized in that: In step S2, the solvent replacement is to use anhydrous ethanol to replace the aqueous solution, and the amount of anhydrous ethanol used is 1.18 times to 1.90 times the mass of silver nitrate added to the silver ammonia solution II.
16. The method for preparing the flaky silver powder with low bulk density according to claim 4, characterized in that: In step S2, the mass concentration of silver ammonia in silver ammonia solution II is 318 g / L; the mass concentration of reducing agent solution II is 180 g / L; and the mass concentration of surfactant solution is 24 g / L-47 g / L.
17. The method for preparing the flaky silver powder with low bulk density according to claim 2, characterized in that: In step S3, the cooling medium of the ball mill external circulation system is cold water, and the circulation speed is 0.5L / min~1L / min.
18. An application of a thin flaky silver powder with low bulk density, characterized in that: The flaky silver powder with low bulk density obtained by the method for preparing flaky silver powder with low bulk density as claimed in any one of claims 2 to 17 is used to produce electronic silver paste.
Citation Information
Patent Citations
Preparation method of low-burnout rate flake silver powder
CN102000827A
Preparation method of flaky silver powder for low-temperature curing silver paste
CN116213744A
Method for preparing size-controllable high-crystallinity flaky silver powder
CN119237726A
Method for preparing silver powder through reduction of hydrazine hydrate with adjustable particle size
CN119566320A
High crystallinity nano-silver particle slurry and its production method
JP2006124787A